Hopf Bifurcation Analysis in a Delayed Kaldor-Kalecki Model of Business Cycle - Kaddar, A.; Talibi Alaoui, H. (Nonlinear Analysis: Modelling and Control, 2008)
In this paper, we analyze the model of business cycle with time delay set forth by A. Krawiec and M. Szydłowski [1]. Our goal in this model is to introduce the time delay into capital stock and gross product in capital accumulation equation. The dynamics are studied in terms of local stability and of the description of the Hopf bifurcation, that is proven to exist as the delay (taken as a parameter of bifurcation) cross some critical value. Additionally we conclude with an application.